2017
DOI: 10.1016/j.juro.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and the Role of Obliterative versus Reconstructive Surgery for Pelvic Organ Prolapse: A National Study

Abstract: Purpose To determine whether frailty affects the type of pelvic organ prolapse (POP) surgery performed and the odds of postoperative complications. Materials and Methods This is a retrospective cohort study of women undergoing obliterative and reconstructive surgery for POP in the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) from 2005 to 2013. We quantified frailty using the NSQIP Frailty Index (NSQIP-FI) and used logistic regression models predicting type of procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…urinary tract infection [UTI], superficial wound infection, pneumonia or blood transfusion) or major (e.g. hospital readmission, return to the operating room, sepsis, deep vein thrombosis [DVT], CVA, reintubation, renal failure, myocardial infarction, pulmonary embolus, dehiscence, cardiac arrest, deep wound infection, coma or death] in accordance with previous studies examining complications using these data [2,7,8,12,1516].…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…urinary tract infection [UTI], superficial wound infection, pneumonia or blood transfusion) or major (e.g. hospital readmission, return to the operating room, sepsis, deep vein thrombosis [DVT], CVA, reintubation, renal failure, myocardial infarction, pulmonary embolus, dehiscence, cardiac arrest, deep wound infection, coma or death] in accordance with previous studies examining complications using these data [2,7,8,12,1516].…”
Section: Methodssupporting
confidence: 82%
“…Several frailty indices have been developed to objectively improve upon the ability to predict postoperative complications among older patients, however, there is a lack of consensus on which index to use. Many studies use the NSQIP frailty index (NSQIP-FI) [2,1216], which is a well-known 11-item cumulative deficits model developed from the 70-item questionnaire from the Canadian Study on Health and Aging. In response to recent changes in ACS-NSQIP variables and a desire to simplify frailty measurement [17,18], other modified frailty indices have been developed including the simplified Frailty Index (sFI) [8,19] and the Risk Analysis Index (RAI) [7].…”
Section: Introductionmentioning
confidence: 99%
“…14,18 We also found an association between increased frailty and higher complications in pelvic organ prolapse surgery. 19 This study is novel in that it investigates the role of frailty specifically with regard to AUS surgery. We found that increased frailty (and not age) was associated with major complications, while age (and not frailty) was associated with minor complications.…”
Section: Discussionmentioning
confidence: 99%
“…For the purposes of this study, we categorized frailty into the following ascending categories: 0, 0.09, 0.18, or ≥0.27 consistent with the literature. 19 The NSQIP-FI specifically assesses frailty and has been shown to correlate well with morbidity and mortality in surgical subspecialties including Urology. 14,20 Additional covariates obtained from NSQIP data included demographic information such as patient age in years (categorized as <65, 65-74, 75-84, ≥85), race (white and non-white), and body mass index (BMI) (underweight [<18.5], normal [18.5-24.9], overweight [25-29.9], and obese [≥30]).…”
Section: Covariatesmentioning
confidence: 99%
“…Reconstructive surgery is the mainstay of treatment for symptomatic pelvic organ prolapse,1 and most surgery is performed transvaginally 2. Prolapse can arise from an isolated segment of the vagina but typically involves several vaginal segments.…”
Section: Introductionmentioning
confidence: 99%